PLACE AND ROLE OF MODERN REGION IN THE GLOBAL ECONOMICAL SYSTEM (International Journal of Innovative Technologies in Economy, 2019)
Economical regional orient has been investigated with considering an economical process forming and organization by the modern period. The role of leading link in this process is played by reproductive structures – regions – but not by industrial ones – enterprises. The very non-commercial structures are leading link in economic sustainable development. Regional oriental- economical system is an element of state, macro regional and global economic spaces that has distinctly expressed hierarchical structure. The development of regional oriental economical system corresponds to cyclic law and undergoes to various influences. The supply of competitiveness of regions influenced by global tendencies supplying oriental unity, sustainability and management is the main challenge in oriental regional development.